Constraints on dispersal and the evolution of the avifauna of the Northern Hemisphere - Böhning-Gaese, Katrin; González-Guzmán, Laura I.; Brown, James H. (Evolutionary ecology, 1998)
One could predict that the capacity for travelling great distances might predispose long-distance migratory birds to be good colonists and to exhibit wider geographic distributions than their non-migratory or short-distance migratory relatives or non-volant mammals. This prediction is not supported by the data on avian biogeography. The distributions of species, genera and families of North American and Eurasian birds and mammals are indeed related to migratory status, but long-distance migratory birds exhibit a great deal of biogeographic regionalism. In particular, at all taxonomic levels their distributions tend to be confined to either the Eastern or Western Hemisphere, suggesting that there has been little successful east-west dispersal between North America and Eurasia. Compared to non-migratory birds, short-distance migratory birds and non-volant mammals, long-distance migrants appear to be subject to severe constraints on their physiology, behaviour and ecology, w hich have prevented colonization of distant regions.[PUBLICATION ABSTRACT]